İslami Üç Faktör Varlık Fiyatlama Modeli: Katılım Endeksi Üzerine Bir Uygulama - Çömlekçi, İstemi; Sondemir, Sedef (Muş Alparslan Üniversitesi, 2020)
Fama French Change in stock return by Three Factor Asset Pricing Model; The excess return on the market's risk-free interest rate is explained by the ratios and the DD / PD ratios. The main aim of this study is to test the validity of the Fama French Three Factor Asset Pricing Model in Islamic finance. It is also aimed to compare the results of the Traditional Fama French Three Factor Asset Pricing Model in the study with the results of the Islamic Fama French Three Factor Asset Pricing Model. In line with this aim, each year between 2011 and 2017, which is included in the KATLM-30 index, 25 share certificates, which are positive in nature and accessible to uninterrupted data, are taken at the end of December. Two separate market portfolios BİST100 and KATLM30 were taken in the study. Islamic Fama French Inflation was obtained instead of the interest rate for the creation of the Three Factor Asset Pricing Model. The monthly data of the stocks obtained were analyzed by the regression analysis method. As a result of the research, the Fama French Three Factor Asset Pricing Model is applied to Islamic financing but not for the period concerned. In the traditional Fama French Three Factor Asset Pricing Model, it has been determined that the market portfolio is valid for the SH, BL, BM and BH portfolios in the model received from BİST100

Fama French Üç Faktör Varlık Fiyatlama Modeline göre hisse senedi getirisindeki değişim; piyasanın risksiz faiz oranı üzerindeki fazla getirisi, ölçek ve DD/PD oranları tarafından açıklanmaktadır. Bu çalışmanın temel amacı Fama French Üç Faktör Varlık Fiyatlama Modelinin İslami finansa uyarlanmasıdır. Çalışmada Geleneksel Fama French Üç Faktör Varlık Fiyatlama Modeli sonuçlarına da ulaşılarak İslami Fama French Üç Faktör Varlık Fiyatlama Modeli sonuçlarıyla karşılaştırılması da amaçlanmaktadır. Bu amaç doğrultusunda KATLM 30 endeksinde yer alan 2011-2017 yılları arasındaki her yıl Aralık ayının sonunda özsermayesi pozitif olan ve kesintisiz verisine ulaşılabilen 25 adet hisse senedi baz alınmıştır. Çalışmada iki ayrı pazar getirisi olarak BIST 100 ve KATLM 30 kullanılmıştır. İslami Fama French Üç Faktör Varlık Fiyatlama Modelinin oluşturulması için faiz oranı yerine enflasyon alınmıştır. Elde edilen hisse senetlerinin aylık verileri regresyon analizi yöntemi ile analiz edilmiştir. Araştırma sonucunda Fama French Üç Faktör Varlık Fiyatlama Modelinin İslami finansa uygulanabilir olduğu ama ilgili dönem için geçerli olmadığı sonucuna ulaşılmıştır. Geleneksel Fama French Üç Faktör Varlık Fiyatlama Modelinde SH, BL, BM ve BH portföylerinde geçerli olduğu tespit edilmiştir
Islamic Three Factor Asset Pricing Model: An Application on Participation Index
anemon
Keywords: ama French Three Factor Asset Pricing Model; Islamic Fama French Three Factor Asset Pricing Model; Participation Index; Fama French Üç Faktör Varlık Fiyatlama Modeli; İslami Fama French Üç Faktör Varlık Fiyatlama Modeli; Katılım Endeksi